Fat Emulsion Infusion Potentiates Coagulation Activation during Human Endotoxemia - van der Poll, Tom; Coyle, Susette M; Levi, Marcel; Boermeester, Marja A; Braxton, Carla C; Jansen, Patty M; Hack, C Erik; Lowry, Stephen F (Thrombosis and Haemostasis, 1996)
Intravenous fat emulsions are frequently given to malnourished patients who are prone to suffer from infectious complications. As injection of low dose endotoxin represents a model to study the human response to acute infection, we sought to determine the effect of lipid emulsion infusion on endotoxin-induced activation of the hemostatic mechanism in man. Ten healthy men received a bolus intravenous injection of endotoxin (lot EC-5; 20 U/kg) midway through a 4-h infusion (125 ml/h) of either dextrose 5% (n = 5) or Intralipid 20% (n = 5). Lipid infusion potentiated endotoxin-induced coagulation activation, as indicated by higher plasma levels of the prothrombin fragment FI + 2 and of thrombin-antithrombin III complexes (both p <0.05 for the difference between groups). However, lipid infusion did not influence the fibrinolytic response to intravenous endotoxin, as reflected by similar increases in the levels of tissue-type plasminogen activator and plas-min-α2-antiplasmin complexes in both groups. Endotoxin-induced appearance of plasminogen activator inhibitor type I was enhanced by lipid infusion (p <0.05). These data suggest that fat emulsion infusion may enhance the tendency towards thrombotic complications in patients with infections.